Multi-color light curves and orbital period research of eclipsing binary V1073 Cyg - Tian, Xiao-Man; Zhu, Li-Ying; Qian, Sheng-Bang; Li, Lin-Jia; Jiang, Lin-Qiao (Research in astronomy and astrophysics, 2018)
New multi-color BVRcIc photometric observations are presented for the W UMa type eclips- ing binary V1073 Cyg. The multi-color light curve analysis with the Wilson-Devinney procedure yielded the absolute parameters of this system, showing that V 1073 Cyg is a shallow contact binary system with a fill-out factor f = 0.124（±0.011）. We collected all available times of light minima spanning 119yr, including CCD data to construct the O - C curve, and performed detailed O - C analysis. The O - C diagram shows that the period change is complex. A long-term continuous decrease and a cyclic vari- ation exist. The period is decreasing at a rate ofP = -1.04（±0.18） × 10-10 d cycle-land, with the period decrease, V1073 Cyg will evolve to the deep contact stage. The cyclic variation with a period of P3 = 82.7（±3.6） yr and an amplitude of A = 0.028（±0.002） d may be explained by magnetic activ- ity of one or both components or the light travel time effect caused by a distant third companion with M3（i1 = 90°） = 0.511 M⊙.